Struktur dan Nilai Sosial dalam Dongeng Cinderella dan Cerita Putri Arabella : Kajian Sastra Bandingan - Ega Setia Nanda; Yenni Hayati (Lingua Susastra, 2020)
Children literature have long been believed to contain values that contribute to shaping the character of the young reader. The children fiction from many countries always offer noble values that can influence the character formation. This study discusses social values in the Cinderella fairy tale (Indonesian version) and the story of Putri Arabella (the Malaysian version). This study used a comparative literature approach to obtain a comprehensive comparison between the fairy tales of Cinderella and Putri Arabela. The data were analyzed using the content analysis method to obtain a sharper and deeper meaning behind the qualitative data in the form of words, phrases, dialogues and narratives. The results of the data analysis found that the two stories both contained social values, the value of compassion, advice to help others, and a sense of responsibility. Besides having similarities, these two stories also contain differences. The differences were found in the characterization and setting of the story. This is because this story originates from two different countries which contain different social conditions.